Safety Features and Inventory Management for Vending Machine Using IoT - et.al, Sazly Anuar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Security features and inventory management for vending machines using IoT is a project which focus mainly on IoT implementation. Although IoT is no stranger to vending machine, the project takes different approach of IoT. It is not just about the inventory management, but also the security features. Since IoT requires internet connection and cloud storage, it requires a microcontroller that supports wireless connection. Therefore, all the operations including controlling the vending machine will be done using ESP32 microcontroller. Anything that are recorded from the vending machine such as the number of product left, the amount of money and the condition of it will be uploaded to the cloud storage, Blynk. Blynk app and cloud storage are easy to use without need of professional knowledge. The inventory management is done by monitoring the amount of the money and items. The safety features will be done using accelerometer and gyroscope, which will be detecting force on the body.